2010
DOI: 10.1002/anie.201001527
|View full text |Cite
|
Sign up to set email alerts
|

Generating Reactive MILs: Isocyanate‐ and Isothiocyanate‐Bearing MILs through Postsynthetic Modification

Abstract: MILs hold up: Robust aluminum‐based metal–organic frameworks (MIL‐53(Al)‐NH2) can undergo postsynthetic modification with phosgene reagents to produce highly reactive, porous materials bearing isocyanate or isothiocyanate groups (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
93
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 42 publications
1
93
0
Order By: Relevance
“…Before measurements all samples were digested in HF/DMSO-d6. 22 Filled circles refer to amino signals, empty circles to azide species and filled squares to isocyanate groups. 1 H-NMR was used to follow the modification of the ligand 70 substitution due to the strong shift of its aromatic protons and to quantify the degree of conversion of azide into isocyanate groups.…”
Section: Scheme 1 Possible Synthetic Routes To Mof With Pendent Isocmentioning
confidence: 99%
See 2 more Smart Citations
“…Before measurements all samples were digested in HF/DMSO-d6. 22 Filled circles refer to amino signals, empty circles to azide species and filled squares to isocyanate groups. 1 H-NMR was used to follow the modification of the ligand 70 substitution due to the strong shift of its aromatic protons and to quantify the degree of conversion of azide into isocyanate groups.…”
Section: Scheme 1 Possible Synthetic Routes To Mof With Pendent Isocmentioning
confidence: 99%
“…On the contrary, strongly electrophilic groups such as isocyanates have been shown to be highly versatile in this respect, allowing the introduction of 30 various carbamate and urea functional groups. 22 The direct synthesis of MOFs possessing such functional groups is difficult, however, so in general these groups are introduced by postsynthetic means. Interestingly, it is possible to transform amino into isocyanate groups in MOFs, but the present method requires 35 the use of diphosgene (route 1 in Scheme 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As described in our earlier studies, modification was confirmed by nuclear magnetic resonance (NMR) spectroscopy. 20,24 …”
mentioning
confidence: 99%
“…Despite significant advances, the majority of PSM reactions have been confined to MOFs bearing a limited variety of functional group ‘handles’ including amines, aldehydes, alkynes, and a few others 17,18. For example, amino-containing MOFs have been converted to amides,4 iso(thio)cyanates,6 ureas,19 imines,10,11 and azides 13. Novel PSM reactions, which originate from alternative functional group handles, is of great value for advancing the utility of PSM and creating MOF materials that are otherwise inaccessible by conventional synthetic approaches.…”
mentioning
confidence: 99%